Pengembangan bahan ajar berbasis pendekatan pendidikan matematika realistik Indonesia (PMRI) pada materi waktu, jarak, dan kecepatan untuk SD kelas V - Asih Duwi Mawartini; Riyadi Riyadi; Joko Daryanto (Universitas Sebelas Maret, 2021)
This study purpose to explain the needs of teachers regarding the teaching materials of mathematics materials time, velocity, and distance based on RME, the validity and practicality of teaching materials developed, the difference in average test results of learners before and after using teaching materials. This research is the research and development of Borg and Gall modified by Sukmadinata with steps: 1) preliminary study, 2) model development, 3) model test. The sample of this study was 5 students of class V of Wirun 04 State Elementary School, Sukoharjo. Data collection techniques are interviews, document analysis, questionnaires, and tests. Data Validity using triangulation of data sources. Data analysis using qualitative descriptive and quantitative descriptive. The results showed that the available teaching materials have not been able to meet the needs of teachers because of minimal practical activities and have not been able to recognize students' thinking ability and have not been in accordance with the concrete level of thinking of elementary school children. The development of mathematical teaching materials material time, distance, and speed is declared valid and practical to be used in the field by experts and is considered effective in improving the achievement of the average value of mathematics learning